ID-Migraine is a sensitive tool for screening migraine among patients with multiple sclerosis - Queiroz, Marcos Vinícius de; Medeiros Jr, Washington Luiz G.; Eboni, Audred C. Biondo; Nogueira, Eduardo A. Guimaraes; Gonçalves, Marcus Vinicius M.; Sousa, Nise Alessandra C.; Fragoso, Yara Dadalti (Headache Medicine, 2019)
Introduction: Migraine and multiple sclerosis (MS) have been described as comorbidities. While other types of headaches can be seen in patients with MS, it is migraine that usually adds to the burden of patients suffering from an already disabling and chronic neurological disease. Migraine is more prevalent in patients with MS than in the general population, and can be worsened by certain treatments that are used to control MS. ID-migraine is a tool to screen migraine in a population. It consists of only three self-reported questions, and shows good sensitivity, specificity and reliability. The aim of the present study was to assess the role of ID-migraine as a potential tool for screening migraine in patients with MS. Method: Patients diagnosed with MS for at least one year were invited to answer ID-migraine. Demographic data and information on MS therapy were obtained at the same time. Results: Sixty-two patients participated in the study. There were 16 men and 46 women, of average age 35 years. Migraine was identified in 51.5% of them and 18% reported having the characteristics of chronic migraine. ID-migraine showed 93% sensitivity and specificity for migraine in this population. The medication most frequently associated with worsening of previous migraine was interferon beta 1-a (27.4% of the cases). Conclusion: ID-migraine was shown to be a potential tool for identifying migraine in patients with MS. However, the high prevalence of migraine in this population may have constituted a selection bias, since most patients without headache may not have felt inclined to participate in this voluntary investigation. The results from this pilot study will be expanded and investigated in more detail in a large national study.